Wireline logs vs drilling events: Which one to believe in implying subsurface pressure? - Agus Mochamad Ramdhan; Arifin Arifin; Rusmawan Suwarman (Indonesian Institute of Sciences, 2021)
As generally known, subsurface pressure can be implied using both wireline logs and drilling events. However, there may be a case where wireline logs and drilling events do not indicate the same subsurface pressure. Data from four vertical wells located in the South Sumatra Basin, Indonesia, were analyzed as a case study. Two wells, Wells A and D, encountered high overpressured zones, confirmed by drilling events and wireline logs data. The two others, Wells B and C, only encountered low overpressured zones, inferred by the relatively low mudweight used during the drilling. However, the wireline logs of Wells B and C show a reversal as Wells A and D. There are two hypotheses to explain the condition in Wells B and C. First, the wireline logs reversal is due to shallow carbonate cementation. Second, Wells B and C were drilled in an unintentional underbalanced condition. The method used includes XRD, SEM, and titration analysis. The results show that the first hypothesis is false, while the second is true. It may be due to some missing information related to drilling events in the final well report of Wells B and C.